SYNTHESIS, CHARACTERIZATION AND ANTIBACTERIAL ACTIVITY OF 2-p-TOLYL-1H-IMIDAZO[4,5f][1,10] PHENANTHROLINE AND ITS Co(II), Ni(II) AND Cu(II) COMPLEXES - Gomleksiz, Mesut; Alkan, Cihan; Erdem, Belgin (Chem Soc Ethiopia, 2013)
In this study, the ligand, 2-p-tolyl-1H-imidazo[4,5-f][1,10] phenanthroline (L) was synthesized by the reaction of 1,10-phenanthroline-5,6-dione with 4-methylbenzaldehyde. The complexes of L were prepared with Co(II), Ni(II) and Cu(II) chlorides. The ligand and its complexes were characterized by IR, UV/VIS, H-1 NMR, TGA, elemental analyses, molar conductivity and magnetic susceptibility. The complexes were proposed to be distorted octahedral geometry. Antibacterial activity of the ligand and its complexes were tested against selected bacteria. The minimum inhibitory concentration (MIC) was determined for the ligand and its complexes.
Keywords: 1,10-Phenanthroline; Imidazole; Cobalt complex; Nickel complex; Copper complex; Antibacterial activity